Case Based Reasoning for Green Information Systems Infusion and Assimilation among IT Professionals in University Campuses - Jnr, Bokolo Anthony; Mazlina, Abdul Majid; Awanis, Romli (Sharif University of Technology, Tehran, I.R. Iran, 2019)
Information Technology (IT) usage in university campuses consume enormous amount of power and incur other costs in cooling and related operations. Currently, universities are infusing environmental friendly initiatives in their campus. However, IT professionals in most universities are still not sure how to infuse and assimilate environmental friendly practices. Hence, Green Information Systems (IS) is suggested as the utilization of technologies and systems for a Greener and more sustainable planet. Accordingly, this study carried out a review on existing Green IS practices and further proposes a decision support framework based on Case Based Reasoning (CBR) technique. The proposed framework utilizes CBR to support the decision making of IT professionals in infusing and assimilating Green IS within university campuses. Findings from this study show how the framework utilizes CBR to support IT professionals in assimilating Green IS lifecycle and infusing Green IS determinants. Furthermore, findings from this study show how IT professionals can Green their university campuses. Moreover, this research study would also be of interest to data and knowledge management community as well as environmental scientists and sustainability researchers.